Judicial Ethics and the Position of Women Judges - Salsa Bella Anjeli (Indonesian Journal for Islamic Studies, 2024)
This study aims to analyze the ethics of judges in the judiciary and the position of female judges which includes knowing the learning system related to the ethics of judges in the judiciary and the position of female judges at SMA N 01 Lebong. The research method used is descriptive qualitative. The results showed that the system in learning the ethics of judges in the judiciary and the position of women judges was good. This is assessed from several things including giving punishment that is in accordance with proper punishment procedures by not physically attacking students, the use of lecture and discussion methods in learning is a test of a teacher's professionalism skills when using oral media, the teams games tournament model in learning that must pay attention to whether it is suitable for the material and suitable for the conditions of students, the existence of media in learning can help and facilitate teachers when delivering learning materials, the suitability of lecture and discussion methods for the material on the ethics of judges in the judiciary and the position of female judges which are considered suitable but must still pay attention to several things, and the determination of suitable methods in learning that still pay attention to learning objectives.